Enriching evaluation practice through care ethics. (April 2020) - Abma, Tineke A.; Visse, Merel; Hanberger, Anders; Simons, Helen; Greene, Jennifer C.
Recently, several authors have called for a critical assessment of the normative dimensions of evaluation practice. This article responds to this call by demonstrating how evaluation practice can be enriched through deliberate engagement with care ethics . Care ethics has a relational and practice view of morality and places caring relationships and responsibilities at the forefront of our being in the world. We will demonstrate how care ethics, in particular Joan Tronto's moral-political theory of democratic caring, can help evaluators to reshape our way of working by placing caring and relationality at the centre of our evaluative work. Care ethics as a normative orientation for evaluation stretches beyond professional codes of conduct, and rule- or principled-based behaviour. It is part of everything we do or not do, how we interact with others, and what kinds of relationships we forge in our practice. This is illustrated with two examples: a democratic evaluation of a programme for refugee children in Sweden; and a responsive evaluation of a programme for neighbours of people with an intellectual disability in The Netherlands. Both examples show that a caring ethos offers a promising pathway to address the larger political, public issues of our times through the interrogation of un-caring practices. We conclude a caring ethos can help evaluators to strengthen a caring society that builds on people's deeply felt need to care, to relate, and to connect within and across communities.